Role of Agency in Developing Social Capital to Increase Food Productivity (Case Study on Krida Taka and Harapan Jaya Farmer Group in Mendik 1) - Saidah Saidah; Sanggar Kanto; Anif Fatma Chawa (Sekolah Pascasarjana Universitas Brawijaya, 2022)
The study aims to describe the shape of the social capital of Krida Taka and Harapan Jaya Farmer Group on Medik 1 Village and analyze how was the role of agency in terms of social capital building for intensifying food production of Krida Taka and Harapan Jaya Farmer Group. The research adopted a qualitative approach, by the case study. Raw data were analyzed by Data Condensation, Data Display, and Verifications. The findings indicated within Krida Taka Farmer Group, through the use of agriculture technology, the social capital was strongly built, individual agency as well as the group has better ability to build social capital, and has high food production. Harapan Jaya Farmer Group showed a different results. Through the use of agriculture technology, it has weak built of social capital through the use of agriculture technology, individual agency as well as group has poor ability to build social capital, and has lower food production.